Metal-Free Synthesis of HMF from Glucose Using the Supercritical CO2-Subcritical H2O-Isopropanol System - Agutaya, J.K.C.N. (American Chemical Society, 2020)
5-Hydroxymethylfurfural (HMF) is a promising building block for the production of biofuels and fine chemicals. While HMF can be derived from biomass, specifically sugars, its synthesis typically requires the use of metal-based catalysts and ionic liquids. In this study, the supercritical CO2-subcritical H2O-isopropanol system was proposed as a green reaction medium for the conversion of glucose to HMF. The response surface methodology based on the Box-Behnken design was used to investigate the effect of temperature, pressure, and isopropanol concentration on the yield of HMF. From the quadratic models, the highest HMF yield was predicted to be 38.3 with a corresponding glucose conversion of 87.5 at 200 Â°C, 16 MPa, and 8 vol isopropanol. A mechanistic study based on the density functional theory was also performed and the results revealed that isopropanol can facilitate the various hydride shifts that occur in the conversion of glucose to HMF. Copyright Â© 2020 American Chemical Society.